Developing the Students' Ability in Reading Through Speed Reading Technique at the First Year Students of SMKN 1 Watunohu - Yunus, Muhammad (USN Kolaka, 2022)
This Classroom Action Research (CAR) aimed to improve first-year students’ reading ability through the application of a speed reading technique at SMKN 1 Watunohu during the 2014/2015 academic year. The participants of this study were 26 first-grade students. The research was conducted in two cycles, each consisting of four stages: planning, acting, observing, and reflecting. Data were collected using observation checklists to examine students’ engagement during the learning process and multiple-choice tests to measure students’ reading achievement. The collected data were analyzed descriptively to evaluate improvements in students’ speed reading performance across the cycles. The findings revealed that in Cycle I, students’ reading ability did not meet the minimum achievement criteria, indicating that the implementation of the technique had not yet been effective. However, significant improvement was observed in Cycle II, where students demonstrated better reading speed and comprehension, and the minimum achievement standard was successfully achieved. These results indicate that the speed reading technique can effectively enhance students’ reading ability when systematically implemented through reflective instructional cycles.This Classroom Action Research (CAR) aimed to improve first-year students’ reading ability through the application of a speed reading technique at SMKN 1 Watunohu during the 2014/2015 academic year. The participants of this study were 26 first-grade students. The research was conducted in two cycles, each consisting of four stages: planning, acting, observing, and reflecting. Data were collected using observation checklists to examine students’ engagement during the learning process and multiple-choice tests to measure students’ reading achievement. The collected data were analyzed descriptively to evaluate improvements in students’ speed reading performance across the cycles. The findings revealed that in Cycle I, students’ reading ability did not meet the minimum achievement criteria, indicating that the implementation of the technique had not yet been effective. However, significant improvement was observed in Cycle II, where students demonstrated better reading speed and comprehension, and the minimum achievement standard was successfully achieved. These results indicate that the speed reading technique can effectively enhance students’ reading ability when systematically implemented through reflective instructional cycles.